2015
DOI: 10.1097/mcp.0000000000000187
|View full text |Cite
|
Sign up to set email alerts
|

Personalized medicine in idiopathic pulmonary fibrosis

Abstract: Clinical management of IPF is unsatisfactory because of limited availability of truly effective therapies, lack of accurate predictors of disease behavior and absence of simple short-term measures of therapeutic response. A number of putative biomarkers have been identified in patients with IPF, although none has been validated to the standard necessary for their use in either therapeutic trials or clinical practice. Currently, ongoing prospective longitudinal studies will hopefully permit such validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 83 publications
0
29
0
2
Order By: Relevance
“…Obtaining representative and diagnostic lung tissue samples with less risk of morbidity and mortality could expand indications and augment the possibility of adding morphological information to data already acquired by clinical investigation, laboratory tests, and HRCT scan [38].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Obtaining representative and diagnostic lung tissue samples with less risk of morbidity and mortality could expand indications and augment the possibility of adding morphological information to data already acquired by clinical investigation, laboratory tests, and HRCT scan [38].…”
Section: Methodsmentioning
confidence: 99%
“…For example, SLB is typically not indicated in subjects having HRCT images demonstrating a typical UIP pattern. However, the availability of TBCB and its lower morbidity compared to SLB could potentially broaden the indication for lung biopsy such as in DPLD patients with equivocal exposures or suspicion of an occult collagen vascular disease who may exhibit histopathological clues to alternative diagnoses (e.g., small granulomas, foci of organizing pneumonia, lymphoid follicles, pulmonary and pleural chronic inflammation) on cryobiopsy that might add weight to other diagnoses [30,38,39]. Therefore, TBCB could sometimes be proposed in patients with a typical radiological UIP pattern, with the aim of collecting more definitive data suggesting occult exposures or collagen vascular diseases.…”
Section: Methodsmentioning
confidence: 99%
“…Fibrosis is a common cause of organ failure in many disease settings, including idiopathic pulmonary fibrosis (Spagnolo et al, 2015), liver cirrhosis (Schuppan, 2015), kidney disease (Ballermann and Obeidat, 2014) and systemic sclerosis (Ebmeier and Horsley, 2015), among others. It is predicted that nearly 45% of all deaths in the developed world are related to chronic fibrosis (Wynn, 2008).…”
Section: Perspectives From Other Organsmentioning
confidence: 99%
“…This approach has garnered increasing attention in the pulmonary community, given its revolutionary impact on the fields of lung cancer, cystic fibrosis, and asthma (9). The term "endotype" was coined by Dr. Gary Anderson to refer to these molecularly defined subgroups, and many investigators now believe that IPF likely contains distinct endotypes that may be identified through biomarker profiles (10)(11)(12).…”
Section: The Promise Of Precision Medicinementioning
confidence: 99%